De sobremesa: From Fauto to modern novel (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
Starting from the connection between modernism and English and German romanticism, as well as from the intertextual relationship between De sobremesa and Faust , this study focuses mainly on how the differences between both works can reproduce doubts that modernism has about modernity, based on Silva's novel. These doubts anticipate, in Silva's case, the avant-garde rupture with the faith on the transcendence of language and art. Taking into account key references of Goethe's work in De sobremesa, I analyze: a) the reasons for modern man's need to embrace the totality of knowledge in order to reach plenitude and its relation to Nietzche; b) the ambiguous relationship between modernism and positivism; and, c)the question of transcendence in art and literature.